Evaluation of physiological quality and vigor of corn seeds coated with chitosan - Lima, Yasmin Chagas; Almeida, Ana Raquel Lopes Soares de; Jacinto Júnior, Silvio Gentil; Bonilla, Oriel Herrera; Lucena, Eliseu Marlônio Pereira de (Revista Principia, 2024)
In favor of better cultures development and productivity, new studies are seeking different alternatives, efficient technologies, and lower environmental impact to achieve such purposes, thus, the present study aimed to evaluate the application effect of a chitosan-based product in the germination and vigor of corn. The study was carried out at the Ceará State University, Campus Itaperi. A completely randomized design was adopted with four replications of 50 seeds, except for the mass, length tests and image analysis carried out in five replications of 20 seeds. Seeds of the cultivar SM 996 were used and submitted to six concentrations of chitosan-based product: 0.0% (control); 0.5%; 1%; 2.5%; 5%; and 10%. It evaluated the following parameters: first count, germination test, radicle, shoot and seedling length and fresh mass, chlorophyll and carotenoid content, electrolyte extravasation, image computerized analysis by Vigor-S®, emergence, and length, fresh and dry mass of the seedlings in a bed. The use of coating with the bioproduct in corn seeds significantly increased the germination test results, the shoots’ first count emerged in a bed, as well as, root and seedlings fresh mass, fresh and dry mass in the field, length of the seedlings in the field, seedlings total length and growth index obtained by the Vigor-S®. It is concluded that the bioproduct presents as an essential bio-stimulant for corn seeds favoring germination parameters, vigor, and development of the seedlings.